Enzymes : A Practical introduction to structure--mechanism-- and data analysis. - Copeland, Robert A (WILEY-VCH, 2000)
This practical, up-to-date survey is designed for a broad spectrum of biological and chemical scientists who are beginning to delve into modern enzymology. Enzymes, Second Edition explains the structural complexities of proteins and enzymes and the mechanisms by which enzymes perform their catalytic functions.